Systemic modelling for relating labour market to vocational education - Evangelos C. Papakitsos (International Journal for Research in Vocational Education and Training (IJRVET), 2016)
The present study introduces a systemic model that demonstrates a description of the relationship between the labour-market and vocational education from the perspective of systemic theory. Based on the application of the relevant methodology, the two open social systems are identified and analyzed. Their key-features are presented and the points of contact are examined and linked, with the purpose to define more efficient manners of interrelation. This study has been conducted using information from the equivalent systems of Greece, as an example, and proposes this systemic method for further research in other countries as well.
Keywords: 330; Labour-market; Systems inquiry; Vocational education; VET; Systemic modelling; Vocational Education and Training